2008
DOI: 10.1002/rcm.3470
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between isomeric triantennary N‐linked glycans by negative ion tandem mass spectrometry and confirmation of glycans containing galactose attached to the bisecting (β1‐4‐GlcNAc) residue in N‐glycans from IgG

Abstract: Negative ion tandem mass spectrometry (MS/MS) spectra of three isomeric triantennary N-linked glycans provided clear differentiation between the isomers and confirmed the occurrence of an isomer that was substituted with galactose on a bisecting GlcNAc (1 --> 4-substituted on the core mannose) residue recently reported by Takegawa et al. from N-glycans released from human immunoglobulin G (IgG). We extend this analysis of human serum IgG to reveal an analogue of the fucosylated triantennary glycan reported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…The presence of a biantennary, bisected N-glycan containing a galactose residue attached to the bisecting GlcNAc (49), first reported by Takegawa et al (2005) from IgG, has also been identified by Harvey et al (2008b) as part of a study into negative ion MS/MS for the differentiation of isomeric triantennary Effect of culture conditions. Glycan structure inferred by "GlycoMod" (Nam, et al, 2008) Chorionic gonadotropin…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 96%
“…The presence of a biantennary, bisected N-glycan containing a galactose residue attached to the bisecting GlcNAc (49), first reported by Takegawa et al (2005) from IgG, has also been identified by Harvey et al (2008b) as part of a study into negative ion MS/MS for the differentiation of isomeric triantennary Effect of culture conditions. Glycan structure inferred by "GlycoMod" (Nam, et al, 2008) Chorionic gonadotropin…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 96%
“…MS/MS fragmentation described by Harvey (48). In negative mode fragmentation spectra of N-glycans, the D ion arises from the loss of the chitobiose core and the substituents forming the 3-antennae; thus the D ion mass corresponds to the composition of the 6-arm antenna as well as the two remaining branching core mannose residues.…”
Section: Alteration Of Membrane Protein Glycosylation In Ovarian Cancermentioning
confidence: 99%
“…The spectra (not shown) of complex N-glycans containing two antennae attached to the 6-linked mannose, such as IV and V, contain an additional ion at [D-36] − of similar relative abundance. [15] This ion, which is sometimes also present in the spectra of glycans containing only one branch at the 6-position is usually of only low abundance. Monoantennary Nlinked glycans with the same composition as those shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The 2,4-di-substituted 3-antenna in compound VIII gives rise to a prominent ion at m/z 831 (termed ion E) as is seen in the spectra of the 3-branched triantennary glycans (XI; Fig. 7c) [15] but which is absent in the spectrum of the normal biantennary isomer (III; Fig. 6b).…”
Section: Glycans Of Composition Hex 5 Hexnac 4 (Viii) and Hex 5 Hexnamentioning
confidence: 97%